If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+2(2x-1)=12
We move all terms to the left:
3x+2(2x-1)-(12)=0
We multiply parentheses
3x+4x-2-12=0
We add all the numbers together, and all the variables
7x-14=0
We move all terms containing x to the left, all other terms to the right
7x=14
x=14/7
x=2
| x²-45+32=0 | | -15x-56=-8x+133 | | 4x+500=5x+400 | | X=5,y=50 | | 6x+19x-10=5(5x+9) | | -12-8w=-2w | | 1.05^x=1.1 | | 2/5x-1/2x=3 | | 19-5h+2=32 | | 2=2(n-4) | | 15/4-7n=9 | | 5u/u=20 | | 1.25q=7.2 | | 10x+70=30x+30 | | 5(-7r-8)=-5 | | 2/3 +b=4/7 | | 1.2-5k=7.2 | | -45=5(-5m-4) | | 14=16m | | -3x+x=6+x | | (f+3)(f-5)=0 | | 6/x+3=-18 | | 21z+12=117 | | 10x+40=20x | | 4(x+7)^2=1 | | 12p+39=11(p=14) | | (f=3)(f-5)=0 | | 2(18-6y)+y=8 | | 9(u-1)=7u+9 | | 9x^2+21x-12=0 | | 10=-5/2-y | | 12=-7x+3(x+8) |